Temporoparietal Fascia Free Flap for a Large Nasal Septal Perforation - Cuccolo, Nicholas G.; Cauley, Ryan P.; Sieber, Brady A.; Hussain, Syed M.D.; Chandler, Laurel K.; Ibrahim, Ahmed M.S.; Lin, Samuel J. (Journal of Reconstructive Microsurgery Open, 2019)
Reconstruction of large nasal septal perforations can be a considerable challenge for surgeons. Reconstructive modalities are often determined by the size of the defect and the quality of local tissue and vasculature. Local and regional flaps may not provide enough tissue to achieve successful closure in patients with large perforations and those with baseline compromise of the nasal mucosa and blood supply from prior intervention or underlying medical condition. Microvascular free tissue transfer is a possible approach to reconstruction in these patients. We report a case of a 30-year-old man who presented with a large, symptomatic, 4 × 3.5 cm perforation as a result of prior functional septoplasty at an outside hospital. Reconstruction of the defect was accomplished in this setting with a free temporoparietal fascia (TPF) flap anastomosed to the columellar branch of the labial artery and the angular vein. Postoperative follow-up visits showed successful closure of the perforation without complications. As illustrated by this case, TPF flap is a versatile tool for complex nasal reconstructions. With minimal donor-site morbidity and rich vascularity capable of promoting remucosalization without the need for prelamination, the TPF flap may be suited for the repair of large nasoseptal perforations.
Keywords: nasal septum reconstruction; temporoparietal fascia flap; microvascular free tissue transfer